A foam copper-supported cobalt nitride catalyst, preparation method and application thereof
By constructing a Co4N composite catalyst on copper foam, the problem of insufficient activity and selectivity of existing electrocatalysts under neutral conditions is solved, and an efficient electrocatalytic nitrate reduction reaction is achieved, with high conversion rate, selectivity and Faradaic efficiency. , and has high performance and stability.
Patent Information
- Application Number
- CN202210996045.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-18
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2042-08-18
AI Technical Summary
It is difficult for existing electrocatalysts to achieve electrocatalytic nitrate reduction reactions with high activity, high selectivity and high Faraday efficiency under neutral conditions, especially inactivation under long-term reaction conditions.
By coupling commercial copper foam with Co4N to construct a composite catalyst, the high specific surface area of copper foam and the high electronic conductivity and electrocatalytic activity of Co4N are used to achieve efficient electrocatalytic nitrate reduction reaction under neutral conditions.
At a low overpotential of 0.29V vs. RHE, the Cu foam@Co4N catalyst exhibits high NO3RR catalytic activity, KNO3-N conversion rate reaches 100%, NH3 selectivity is as high as 94.4%, Faradaic efficiency is greater than 90%, and has high performance stability.
Smart Images

Figure CN115323403B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalyst preparation, and in particular relates to a foam copper-supported cobalt nitride catalyst, a preparation method and an application thereof. Background Art
[0002] Ammonia (NH3), as a key value-added chemical, is essential for the production of fertilizers and is a potential energy carrier. The current large-scale production of NH3 mainly relies on the energy-intensive Haber-Bosch process, which involves high temperature and high pressure reactions and leads to large energy consumption and serious environmental problems. Inspired by natural microbial N2 fixation, the electrochemical decomposition of water (H2O) produces protons and subsequent N2 reduction under ambient conditions. Therefore, the synthesis of NH3 via nitrogen (N2)-water electrochemical reactions has stimulated the research interests of researchers. However, due to the high dissociation energy of the N≡N bond (941 kJ mol -1 ) and the ultra-low solubility of N2 result in low NH3 yield and selectivity, which is 2-3 orders of magnitude lower than that of the Haber-Bosch process. Therefore, synthesizing NH3 directly from non-N2 electrochemical reactions can circumvent these challenges. When looking for nitrogen-containing substitutes in H2O-based electrochemical reactions, nitrate anions (NO3 - ) stands out because the dissociation energy of the N=O bond is relatively low (204 kJ mol) compared to the N≡N bond. -1 ), indicating that the reaction kinetics of producing NH3 is better. The treatment of nitrate-containing domestic and industrial wastewater makes nitrate (NO3 - ) has become a common pollutant in surface water and underground aquifers. Nitrate pollution is a serious environmental problem that is detrimental to the supply of water and food and even endangers human health. Therefore, under environmental conditions, NO3 - Efficient conversion to NH3 has important scientific and practical significance, not only reducing energy consumption, but also helping to solve environmental pollution problems. In the context of energy crisis and CO2 emission reduction, electrocatalytic reduction of nitrates for sustainable ammonia production is a particularly promising option.
[0003] At present, researchers have made great efforts in the rational design and construction of efficient NO3RR electrocatalysts. The chemical composition of electrode materials plays a crucial role in the efficiency and product selectivity of NO3RR. It is very necessary to develop efficient and stable NO3RR electrocatalysts. Precious metal (such as Pt, Ag, Pd and Rh) based electrode materials usually show excellent activity for NO3RR, but the high cost and scarcity of precious metals limit their practical application. Therefore, the development of promising non-precious metal electrocatalysts for NO3RR has aroused great interest. At present, various non-precious metal (such as Cu, Ni, Co, Fe) based electrocatalysts are widely used to produce NH3 in NO3RR due to their good activity, adjustable electronic structure and low cost, especially under alkaline conditions. However, under neutral conditions, these electrocatalysts may be deactivated due to leaching and surface poisoning under long-term reaction conditions, resulting in low selectivity for the production of ammonia. In addition, there is also a competitive HER reaction in the NO3RR process, resulting in low Faradaic efficiency. Copper-based catalysts have good binding to NO3 - And catalyze NO3 - Converted to NO2 - The ability to be used in NO3 - However, pure copper catalysts usually deactivate quickly due to their high sensitivity to NO3RR intermediates such as NO2 - and NO), so these limitations are alleviated by forming a complex between Cu and transition metal compounds to regulate proton or electron transfer and the binding strength of partially reduced intermediates adsorbed on the Cu center. Co4N has good electronic conductivity, and the bonding of N atoms to Co atoms changes the d-band structure of metal Co, resulting in a contraction of the d-band, which makes the density of states near the Fermi level higher and exhibits high electrocatalytic activity. However, the construction of Cu and Co4N composite catalysts in efficient electrocatalysis of NO3 - The application research of reduction reaction has always been in a blank stage. Therefore, it is very important to construct Cu and Co4N composite catalysts through a simple preparation method to improve the activity, selectivity and Faraday efficiency of electrocatalytic nitrate reduction to produce ammonia for industrial production.
[0004] Therefore, the problems and defects of the prior art are: it is still a huge challenge for the existing electrocatalysts to simultaneously obtain high activity, high selectivity and high Faraday efficiency for the electrocatalytic nitrate reduction reaction in a neutral system. Summary of the invention
[0005] In view of the problems existing in the prior art, the present invention provides a foam copper-loaded cobalt nitride catalyst, a preparation method and an application thereof.
[0006] The present invention is achieved in that a method for preparing a foam copper-supported cobalt nitride catalyst comprises:
[0007] 1) Weigh cobalt nitrate hexahydrate, urea and ammonium fluoride, dissolve in deionized water, and stir to form a mixed solution;
[0008] 2) subjecting the pretreated copper foam to a hydrothermal reaction with the mixed solution prepared in step 1);
[0009] 3) Washing and drying the copper foam in step 2) to obtain a precursor, and annealing the precursor in an ammonia atmosphere to obtain a copper foam-supported cobalt nitride catalyst.
[0010] Furthermore, the molar ratio of cobalt nitrate hexahydrate, urea and ammonium fluoride in step 1) is 1:2:3-5.
[0011] Furthermore, the specific molar ratio of cobalt nitrate hexahydrate, urea and ammonium fluoride in step 1) is 1:2:5.
[0012] Furthermore, the temperature of the hydrothermal reaction in step 2) is 80° C. to 200° C., and the reaction time is 5 h to 15 h.
[0013] Furthermore, the hydrothermal reaction temperature in step 2) is 120° C. and the reaction time is 6 h.
[0014] Further, the pretreatment method of the copper foam in step 2) is:
[0015] The oxide layer on the surface of the copper foam was removed by ultrasonic cleaning with 0.1 M dilute hydrochloric acid, wherein the area of the copper foam was 2.5 cm*4 cm, and the ultrasonic time was 30 min.
[0016] Furthermore, in the step 3), the annealing temperature is 300° C. to 600° C., and the annealing time is 2 h to 4 h.
[0017] Furthermore, in the step 3), the annealing temperature is 500° C. and the annealing time is 3 hours.
[0018] In combination with the above technical solutions and the technical problems solved, please analyze the advantages and positive effects of the technical solutions to be protected by the present invention from the following aspects:
[0019] First, in view of the technical problems existing in the above-mentioned prior art and the difficulty of solving the problems, the technical solutions to be protected by the present invention and the results and data during the research and development process are closely combined to analyze in detail and deeply how the technical solutions of the present invention solve the technical problems, and some creative technical effects brought about after solving the problems. The specific description is as follows:
[0020] Pure copper has good binding with NO3 - And catalyze NO3- Converted to NO2 - The ability of the catalyst to react with the catalyst is limited, but the production of intermediate toxic byproducts usually leads to rapid deactivation. This limitation is alleviated by coupling with Co4N, which has good electronic conductivity and electrocatalytic activity. The present invention uses commercial copper foam as a substrate to load Co4N to construct a composite catalyst, and through the coupling of two components, it can achieve high activity, high selectivity, high Faraday efficiency and high stability of electrocatalytic NO3RR reaction under neutral conditions. In a 0.1M_K2SO4 electrolyte containing 100ppm KNO3-N, Cu foam@Co4N exhibits high NO3RR catalytic activity, high conversion rate, high Faraday efficiency and high NH3 selectivity at low overpotential. At 0.29V vs.RHE, the KNO3-N conversion rate reaches 100%, the NH3 selectivity is as high as 94.4%, the Faraday efficiency is greater than 90%, and it has high performance stability.
[0021] Second, considering the technical solution as a whole or from the perspective of the product, the technical effects and advantages of the technical solution to be protected by the present invention are described in detail as follows:
[0022] Ammonia is a key value-added chemical that is required for the production of fertilizers and is a potential energy carrier. Nitrate pollution is a serious environmental problem and even a hazard to human health. Therefore, it is necessary to convert NO3 into nitrate by electrocatalysts under ambient conditions. - Efficient conversion to NH3 not only reduces energy consumption but also helps solve environmental pollution problems. It is a particularly promising option for sustainable ammonia production so that it can be used in industrial production and thus bring higher commercial value.
[0023] The present invention uses a simple hydrothermal reaction and nitridation treatment to synthesize a copper foam loaded with cobalt nitride (Cu foam@Co4N) composite catalyst from commercial copper foam. The invention has a simple preparation method, abundant raw material sources, low price, and excellent catalytic performance for nitrate reduction to synthesize ammonia, which can achieve green synthesis of NH3 while removing nitrate pollutants. The invention increases the conversion rate of 100ppm KNO3-N to 100.0% under neutral conditions and a low overpotential of 0.29V vs.RHE, the NH3 selectivity is 94.4%, the Faraday efficiency is 90.52%, and its performance stability is relatively high.
[0024] Third, as auxiliary evidence of the inventiveness of the claims of the present invention, it is also reflected in the following important aspects:
[0025] (1) The expected benefits and commercial value of the technical solution of the present invention after transformation are as follows: Studies have shown that the commercial feasibility of electrocatalytic reduction of nitrate to ammonia is relatively high. Ammonia has a clear market demand. Ammonia is a key value-added chemical and occupies an important position in the national economy. Nitrogen fertilizers used in agriculture, such as urea, ammonium nitrate, ammonium phosphate, ammonium chloride and various ammonia-containing compound fertilizers, are all produced with ammonia as raw material. Synthetic ammonia is one of the bulk chemical products. The world's annual synthetic ammonia production has reached more than 100 million tons, of which about 80% of ammonia is used to produce chemical fertilizers and 20% is used as raw materials for other chemical products. In addition, ammonia is a potential energy carrier. Nitrate pollution is a serious environmental problem. It is not conducive to the supply of water and food, and even endangers human health. Therefore, under environmental conditions, NO3 - Efficient conversion to NH3 has important scientific and practical significance, not only reducing energy consumption, but also helping to solve environmental pollution problems, with considerable expected benefits and high commercial value. In the context of energy crisis and carbon dioxide emission reduction, electrocatalytic reduction of nitrates for sustainable ammonia production is a particularly promising option.
[0026] The technical solution of the present invention is to construct cobalt nitride on the foam copper with large specific surface area so that Cu and Co4N are coupled to electrocatalyze nitrate reduction to produce ammonia. The catalyst preparation process is simple and the electrocatalytic NO3 - The high selectivity and activity of reduction are expected to realize industrial-grade mass production of ammonia. In addition, photovoltaic cells can be used to supply electricity to reduce electricity consumption, and industrial-grade ammonia preparation can be achieved through the concentration and separation of ammonia for application in agriculture, chemical industry and other industries.
[0027] (2) The technical solution of the present invention solves a technical problem that people have been eager to solve but have never succeeded in solving: the existing electrocatalysts generally have high electrocatalytic nitrate reduction activity to synthesize ammonia in alkaline electrolytes, but in neutral systems, they either have high Faraday efficiency and low NH4 + Selectivity, either high NH4 + Therefore, it is still a great challenge to simultaneously obtain high activity, high selectivity and high Faradaic efficiency for the electrocatalytic nitrate reduction reaction to produce ammonia. Pure copper has good binding capacity for NO3 - And catalyze NO3 - Converted to NO2 - However, due to the production of intermediate toxic byproducts, the catalyst usually deactivates quickly. This limitation is alleviated by coupling with Co4N, which has good electronic conductivity and electrocatalytic activity. The technical solution of the present invention uses a simple preparation method to construct a Cu and Co4N composite catalyst, and through coupled catalysis, the activity, selectivity and Faraday efficiency of electrocatalytic nitrate reduction to produce ammonia are improved for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a flow chart of a method for preparing a foam copper-supported cobalt nitride catalyst provided by an embodiment of the present invention;
[0029] Figure 2 is the X-ray diffraction pattern of Cu foam@Co4N prepared in Example 1 of the present invention;
[0030] Figure 3 is a scanning electron microscope image of Cu foam@Co4N prepared in Example 1 of the present invention and Carbon paper@Co4N prepared in Comparative Example 1;
[0031] Figure 4 It is the LSV curve of Cu foam@Co4N prepared in Example 1 of the present invention in 0.1M K2SO4 and 0.1MK2SO4+100ppmKNO3-N electrolyte;
[0032] Figure 5 The graph is a graph of NO3-N conversion and Faraday efficiency of Cu foam@Co4N prepared in Example 1 of the present invention, Carbon paper@Co4N prepared in Comparative Example 1, and pure foam copper in 0.1M K2SO4+100ppm KNO3-N electrolyte;
[0033] Figure 6 The NH3 selectivity and Faraday efficiency of the Cu foam@Co4N prepared in Example 1 of the present invention in 7 consecutive cycle tests in 0.1M K2SO4+100ppm KNO3-N electrolyte are shown. DETAILED DESCRIPTION
[0034] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0035] 1. Explanatory Examples In order to enable those skilled in the art to fully understand how to implement the present invention, this section provides an illustrative example that expands and describes the technical solution of the claims.
[0036] like Figure 1 As shown, the preparation method of the foam copper supported cobalt nitride catalyst provided by the embodiment of the present invention comprises:
[0037] S101, weighing cobalt nitrate hexahydrate, urea and ammonium fluoride, dissolving them in deionized water, and stirring to form a mixed solution;
[0038] S102, subjecting the pretreated copper foam to a hydrothermal reaction with the mixed solution prepared in step S101;
[0039] S103, washing and drying the foamed copper in step S102 to obtain a precursor, and annealing the precursor in an ammonia atmosphere to obtain a foamed copper-supported cobalt nitride catalyst.
[0040] In the step S101 of the embodiment of the present invention, the molar ratio of cobalt nitrate hexahydrate, urea and ammonium fluoride is 1:2:3-5, preferably 1:2:5.
[0041] The temperature of the hydrothermal reaction in step S102 in the embodiment of the present invention is 80° C. to 200° C., preferably 120° C., and the reaction time is 5 h to 15 h, preferably 6 h.
[0042] The pretreatment method of the copper foam in step S102 in the embodiment of the present invention is:
[0043] The oxide layer on the surface of the copper foam was removed by ultrasonic cleaning with 0.1 M dilute hydrochloric acid, wherein the area of the copper foam was 2.5 cm*4 cm, and the ultrasonic time was 30 min.
[0044] In step S103 in the embodiment of the present invention, the annealing temperature is 300° C. to 600° C., preferably 500° C., and the annealing time is 2 h to 4 h, preferably 3 h.
[0045] 2. Application Examples: In order to prove the creativity and technical value of the technical solution of the present invention, this section provides application examples of the technical solution of the claims on specific products or related technologies.
[0046] The invention discloses a foam copper-supported cobalt nitride high-efficiency electrocatalyst for synthesizing ammonia by nitrate reduction. The foam copper-supported cobalt nitride high-efficiency electrocatalyst for synthesizing ammonia by nitrate reduction adopts a foam copper-supported cobalt nitride composite catalyst.
[0047] Application Example 1:
[0048] The method for preparing the foam copper-supported cobalt nitride catalyst of Example 1 comprises the following steps:
[0049] 1) Weigh cobalt nitrate hexahydrate, urea and ammonium fluoride in a molar ratio of 1:2:5 and dissolve in 30 ml of deionized water, stirring to form a mixed solution;
[0050] 2) The copper foam with an area of 2.5 cm*4 cm was ultrasonically cleaned with 0.1 M dilute hydrochloric acid for 30 min to remove the oxide layer on the surface of the copper foam, and then subjected to hydrothermal reaction with the mixed solution prepared in step 1) at 120° C. for 6 h;
[0051] 3) The copper foam in step 2) is rinsed with deionized water and dried to obtain a precursor, and the precursor is annealed at 500° C. for 3 h in an ammonia atmosphere to obtain a Cu foam@Co4N catalyst.
[0052] Comparative Example 1:
[0053] The preparation method of carbon paper-supported cobalt nitride of Comparative Example 1 comprises the following steps:
[0054] 1) Weigh cobalt nitrate hexahydrate, urea and ammonium fluoride in a molar ratio of 1:2:5 and dissolve in 30 ml of deionized water, stirring to form a mixed solution;
[0055] 2) using acetone to ultrasonically clean a carbon paper with an area of 2.5 cm*4 cm for 30 min to remove grease on the surface of the carbon paper, and then hydrothermally reacting the carbon paper with the mixed solution prepared in step 1) at 120° C. for 6 h;
[0056] 3) The carbon paper in step 2) is rinsed with deionized water and dried to obtain a precursor, and the precursor is annealed at 500° C. for 3 h in an ammonia atmosphere to obtain a Carbon paper@Co4N catalyst.
[0057] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Any modifications, equivalent substitutions and improvements made by any technician familiar with the technical field within the technical scope disclosed by the present invention and within the spirit and principle of the present invention should be covered by the protection scope of the present invention.
[0058] 3. Evidence of the effects of the embodiments. The embodiments of the present invention have achieved some positive effects during the development or use process, and indeed have great advantages over the prior art. The following content is described in conjunction with the data, charts, etc. of the test process.
[0059] Figure 1 This is the technical roadmap of the Cu foam@Co4N composite catalyst prepared in Example 1.
[0060] Figure 2 This is the XRD pattern of Cu foam@Co4N prepared in Example 1, which shows the characteristic diffraction peaks of Cu and Co4N, which fully demonstrates that the foam copper is loaded with cobalt nitride after hydrothermal and ammonia atmosphere annealing.
[0061] Figure 3 This is a scanning electron microscope image of Cu foam@Co4N prepared in Example 1. It can be clearly seen from the image that the surface of the foam copper is coated with a rough nanowire array. This unique nanowire array can provide a more efficient pathway for mass and charge transfer during NO3RR.
[0062] Figure 4The LSV curves of Cu foam@Co4N prepared in Example 1 in 0.1M K2SO4 and 0.1M K2SO4+100ppm KNO3-N electrolytes show that the starting potential of LSV shifts positively when 100ppm KNO3-N is present in the electrolyte, which indicates that NO3 - Reduction reaction to NO3 - The main process of existence.
[0063] Figure 5 NO3 in 0.1M K2SO4+100ppm KNO3-N electrolyte for Cu foam@Co4N prepared in Example 1, Carbon paper@Co4N prepared in Comparative Example 1, and bare Cufoam - Conversion and Faraday efficiency diagram (from top to bottom: Cufoam@Co4N, Carbon paper@Co4N and bare Cu foam). For the Cu foam@Co4N electrocatalyst, high conversion, high Faraday efficiency and high NH3 selectivity are shown at low overpotentials. At 0.29V vs.RHE, the KNO3-N conversion rate reaches 100%, the NH3 selectivity is as high as 94.4%, and the Faraday efficiency is greater than 90%. For the Carbon paper@Co4N electrocatalyst, with the increase of potential, the KNO3-N conversion rate gradually increases, and the NH3 selectivity also gradually increases, but its selectivity never exceeds 70%, and its Faraday efficiency is always below 70%. For bare Cu foam, its Faraday efficiency is always below 50%. Before -0.39V vs.RHE, the KNO3-N conversion rate keeps increasing, but NO2 - The selectivity is always higher than NH4 + , indicating that NO2 - The Cu active sites of bare Cu foam are poisoned, preventing them from transferring to NH4 + After the potential is higher than -0.39V vs.RHE, the conversion rate of KNO3-N decreases and the Faraday efficiency decreases, indicating that the competitive reaction HER increases with the increase of potential. This figure shows that the Cu foam@Co4N electrocatalyst exhibits high conversion rate, high NH3 selectivity and high Faraday efficiency through simple Cu foam and Co4N catalytic coupling, that is, Cu foam@Co4N has efficient NO3RR catalytic performance.
[0064] Figure 6The figure shows the NH3 selectivity and Faraday efficiency of the Cu foam@Co4N prepared in Example 1 in 7 consecutive cycle tests in 0.1M K2SO4+100ppm KNO3-N electrolyte. The figure shows that after 7 cycle tests, the NH3 selectivity and Faraday efficiency of Cu foam@Co4N have no attenuation, indicating that Cu foam@Co4N has good performance stability.
[0065] The above experimental data show that the Cu foam@Co4N prepared in Example 1 has good electrocatalytic nitrate reduction performance.
Claims
1. A method for preparing a foam copper-supported cobalt nitride catalyst, characterized in that: The preparation method of the foam copper-supported cobalt nitride catalyst comprises: 1) Weigh cobalt nitrate hexahydrate, urea and ammonium fluoride, dissolve in deionized water, and stir to form a mixed solution; 2) subjecting the pretreated copper foam to a hydrothermal reaction with the mixed solution prepared in step 1); 3) washing and drying the copper foam in step 2) to obtain a precursor, and annealing the precursor in an ammonia atmosphere to obtain a copper foam supported cobalt nitride catalyst; The molar ratio of cobalt nitrate hexahydrate, urea and ammonium fluoride in step 1) is 1:2:3-5; The temperature of the hydrothermal reaction in step 2) is 80°C to 200°C, and the reaction time is 5h to 15h; In the step 3), the annealing temperature is 300° C. to 600° C., and the annealing time is 2 h to 4 h.
2. The method for preparing a foam copper-supported cobalt nitride catalyst according to claim 1, characterized in that: The pretreatment method of the copper foam in step 2) is: The oxide layer on the surface of the copper foam was removed by ultrasonic cleaning with 0.1 M dilute hydrochloric acid, wherein the area of the copper foam was 2.5 cm*4 cm, and the ultrasonic time was 30 min.
3. The method for preparing a foam copper-supported cobalt nitride catalyst according to claim 1, wherein: The specific molar ratio of cobalt nitrate hexahydrate, urea and ammonium fluoride in step 1) is 1:2:
5.
4. The method for preparing a foam copper-supported cobalt nitride catalyst according to claim 1, characterized in that: The hydrothermal reaction temperature in step 2) is 120° C. and the reaction time is 6 hours.
5. The method for preparing a foam copper-supported cobalt nitride catalyst according to claim 1, characterized in that: In the step 3), the annealing temperature is 500° C. and the annealing time is 3 hours.
6. A foam copper supported cobalt nitride catalyst, characterized in that: The foam copper-supported cobalt nitride catalyst is prepared by the preparation method of the foam copper-supported cobalt nitride catalyst according to any one of claims 1 to 5.
7. A foam copper-supported cobalt nitride-based highly efficient electrocatalyst for nitrate reduction and ammonia synthesis, characterized in that: The foam copper-supported cobalt nitride high-efficiency nitrate reduction ammonia synthesis electrocatalyst adopts the foam copper-supported cobalt nitride catalyst described in claim 6.
Citation Information
Patent Citations
Manufacturing method of copper, cobalt nitride and carbon in-situ composite electrode
CN109546157A
Self-supporting transition metal nitride composite material, preparation method and application of self-supporting transition metal nitride composite material in electro-catalytic hydrogen evolution
CN113502503A